2021
DOI: 10.3390/nu13114044
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intake and Serum Levels of Copper, Selenium and Zinc According to Glucose Metabolism: Cross-Sectional and Comparative Study

Abstract: Trace elements play an important role in metabolism. We compared the daily intake and serum concentrations of copper (Cu), selenium (Se), and zinc (Zn) across a spectrum of glucose tolerance status in a representative U.S. population. Daily intake and serum concentrations of Cu, Zn and Se in 5087 adults from the 2011–2016 National Health and Nutrition Examination Survey (NHANES) were examined and compared to normal (NGT) and abnormal (AGT) glucose tolerance and the presence of diabetes mellitus (DM). Other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Dietary copper is a redox active metal and has been shown to cause impaired glucose metabolism in mechanistic and observational studies [ 22 25 ]. Our results conform to another NHANES report in approximately 5000 US adults showing higher serum copper, selenium, and zinc to be associated with abnormal glucose metabolism [ 26 ]. In another cross-sectional study of 1197 adults recruited in Italy, dietary copper revealed a significant positive association with C-reactive protein [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Dietary copper is a redox active metal and has been shown to cause impaired glucose metabolism in mechanistic and observational studies [ 22 25 ]. Our results conform to another NHANES report in approximately 5000 US adults showing higher serum copper, selenium, and zinc to be associated with abnormal glucose metabolism [ 26 ]. In another cross-sectional study of 1197 adults recruited in Italy, dietary copper revealed a significant positive association with C-reactive protein [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that ZnMet had a higher bioavailability among zinc sources ( 41 ); therefore, we further detected the concentration of zinc in serum and tissues, which can reflect the absorption and utilization of zinc and is also used as an indicator to evaluate the nutritional status of the body ( 42 ). An increase in serum zinc concentration indicates that zinc metabolism is enhanced ( 43 ). In this study, whether it is serum zinc or serum iron, the ZnMet group has the highest content, indicating that the addition of ZnMet improved the absorption of trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…They involved in the regulation of the innate and adaptive immune responses. Many studies have reported that the serum level of Cu and Zn are associated with health outcomes including osteoporosis(8), basic physical functioning (11) and glucose metabolism (12). To date, a few studies have attempted to explore the association between Cu and Zn and risk of OA or RA with inconsistent results (7,13,14).…”
Section: Introductionmentioning
confidence: 99%